2017
DOI: 10.3390/ijms18050977
|View full text |Cite
|
Sign up to set email alerts
|

miR-365 Ameliorates Dexamethasone-Induced Suppression of Osteogenesis in MC3T3-E1 Cells by Targeting HDAC4

Abstract: Glucocorticoid administration is the leading cause of secondary osteoporosis. In this study, we tested the hypotheses that histone deacetylase 4 (HDAC4) is associated with glucocorticoid-induced bone loss and that HDAC4 dependent bone loss can be ameliorated by miRNA-365. Our previous studies showed that miR-365 mediates mechanical stimulation of chondrocyte proliferation and differentiation by targeting HDAC4. However, it is not clear whether miR-365 has an effect on glucocorticoid-induced osteoporosis. We ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(27 citation statements)
references
References 30 publications
0
27
0
Order By: Relevance
“…Our study demonstrated that overexpression of miR-221 promoted osteoblast proliferation. In line with this finding, Xu et al ( 25 ) showed that transfection of MC3T3-E1 osteoblasts with miR-365 ameliorated dexamethasone-induced inhibition of cell viability. Cyclins and CDKs are known to be regulators of cell cycle.…”
Section: Discussionmentioning
confidence: 68%
“…Our study demonstrated that overexpression of miR-221 promoted osteoblast proliferation. In line with this finding, Xu et al ( 25 ) showed that transfection of MC3T3-E1 osteoblasts with miR-365 ameliorated dexamethasone-induced inhibition of cell viability. Cyclins and CDKs are known to be regulators of cell cycle.…”
Section: Discussionmentioning
confidence: 68%
“…They are considered to function as mRNA regulators by interacting with the 3'-untranslated region (3'UTR) of the targeted mRNA transcript and leading to degradation (2)(3)(4)(5). Several, if not all, biological processes are reported to be regulated by miRNAs, including cell cycle, proliferation, metabolism, immune response, hematopoiesis and differentiation (6)(7)(8)(9)(10). It is widely accepted that miRNAs are vital in the process of tumorigenesis by targeting key factors (11,12).…”
Section: Introductionmentioning
confidence: 99%
“…Previously, several studies demonstrated that miRNAs take part in many biological processes by negatively regulating target genes through interaction with the 3′-untranslated regions (3′-UTR) of the target mRNAs [ 33 , 34 , 35 ]. To further explore detailed molecular mechanisms that miR-125a-5p inhibits porcine intramuscular preadipocytes differentiation, we predicted target genes of miR-125a-5p using TargetScan 7.1.…”
Section: Resultsmentioning
confidence: 99%